Improving the Iraqi Oil Well Cement Properties Using Barolift: an Experimental Investigation - Hadi, Ali M.; Al-Haleem, Ayad A. (Iraqi Journal of Science, 2021)
Cement is a major component in oil and gas drilling operations that is used to maintain the integrity of boreholes by preventing the movement of formation fluids through the annular space and outside the casing. In 2019, Iraq National Oil Company ordered all international oil and gas companies which are working in Iraq to use Iraqi cement (made in Iraq) in all Iraqi oil fields; however, the X-ray fluorescence (XRF) and compressive strength results in this study show that this cement is not matching with American Petroleum Institute (API) standards. During this study, barolift was used to improve the properties of Iraqi cement used in oil wells at high pressure and high temperature (HPHT). Barolift (1 g) was added to cement admixture to evaluate its influence on improving the performance of cement, mainly related to the property of toughness. Primarily, the quality and quantity of cement contents were determined using X-ray fluorescence. Experiments were conducted to examine the characteristics of the base cement and the cement system containing 1g of barolift, such as thickening time, free water, compressive strength, and porosity. X-ray diffraction (XRD), scanning electron microscope (SEM), and energy dispersive X-ray spectroscopy (EDS) were conducted for analyzing the microstructure of cement powder. The experimental results showed that barolift acted as a retarder and improved the thickening time, slightly increased the free water, enhanced the mechanical properties, reduced the porosity, and aided in scheming new cement slurry to withstand the HPHT conditions. Microstructure analysis showed that barolift particles blocked the capillaries by filling cement spaces and, thus, a denser and stricter cement network was achieved.